CAFF Technical Report No.9 - Seabird Harvest Regimes in the Circumpolar Nations - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (Conservation of Arctic Flora and Fauna Working Group (CAFF), 2001)
Arctic Council's CAFF Working Group's Technical Report No.9 - Seabird Harvest Regimes in the Circumpolar Nations, published 2001